2021
DOI: 10.1186/s40359-021-00654-y
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and socio-emotional correlates of psychological well-being and mental health in Guatemalan adults

Abstract: Background Little is known about associations of psychological and mental well-being with cognitive and socioemotional factors in low and middle-income countries, particularly among vulnerable populations born in adverse environments that may restrict developmental potential. This study aimed to examine the cognitive and socioemotional correlates of psychological well-being and mental health in a cohort of Guatemalan adults born in contexts of poverty and malnutrition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Contrasting results have been reported concerning the association between mental health and religiosity. Despite the number of studies suggesting that religion or spirituality might contribute to better mental health and well-being [33][34][35][36], studies on religious coping during the COVID-19 pandemic have reported negative effects on mental health [24,37].…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting results have been reported concerning the association between mental health and religiosity. Despite the number of studies suggesting that religion or spirituality might contribute to better mental health and well-being [33][34][35][36], studies on religious coping during the COVID-19 pandemic have reported negative effects on mental health [24,37].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, mental health and mental health care-seeking are widely stigmatized in the Arab culture ( 24 ), yet Arab refugees often turn to faith-based coping for their mental health ( 25 ). The benefits of spirituality and faith-based coping of disease are well documented in the literature ( 26 28 ) and faith has been specifically shown to promote preservation of self among individuals with dementia ( 29 ). Thus, understanding the utilization of spirituality as a tool to improve mental and cognitive wellbeing among Arab refugees can yield insightful information to be integrated in public mental health for this population.…”
Section: Introductionmentioning
confidence: 99%